Membangun Model Penyelesaian Perkara Pidana melalui Keadilan Restoratif oleh Kepolisian Berdasarkan Asas Dualistik - Teguh Pribadi Tjahjana; Yusuf M. Said (FOCUS, 2026)
The current condition of law enforcement has not fully achieved fair legal certainty, indicating the need to strengthen the restorative justice approach in the development of national criminal law. This study examines the relevance of restorative justice within the framework of Law Number 1 of 2023 on the National Criminal Code, which adopts a dualistic doctrine separating criminal acts (actus reus) from fault (mens rea). The research focuses on the significance of restorative justice in the national criminal justice system and the ideal model of its application in line with the dualistic principle. Using normative legal research with statutory and conceptual approaches, the study finds that litigation-based case settlement often fails to deliver substantive justice. Therefore, restorative justice emerges as a necessary alternative. When applied consistently with the dualistic doctrine, restorative justice allows reconciliation to function as a basis for eliminating fault and criminal liability, thereby supporting the realization of fair legal certainty as a constitutional legal ideal..